Literacy Rate by Sex in Jharkhand, 2011: Examining the Gender Disparity in Literacy Rates across Districts in Jharkhand, 2011 (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The research tried to measure the spatial pattern of literacy rate and differential in literacy rates in males and females of Jharkhand in 2011. Data pertaining to literacy rate is collected from the census of India at the district level. According to 2011, Ranchi district has the largest literacy rate of 77.13 per cent while Giridih 65.12 per cent has the lowest literacy rates.